PENGGUNAAN BAHASA GAUL GEN Z DI TIKTOK DAN DAMPAKNYA TERHADAP EKSISTENSI BAHASA INDONESIA DI ERA DIGITAL - Fitriani, Naila; Ramadhani, Suhaila; Tasya; Suriani, Ari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology has significantly transformed communication patterns, particularly among Generation Z, who actively use social media as a primary means of interaction. TikTok has become one of the leading platforms that encourages the emergence and growth of slang among young people. This study aims to analyze the use of slang by Generation Z on TikTok and examine its impact on the existence of the Indonesian language in the digital era. This research employs a qualitative approach using a literature review method by examining various journals, scholarly articles, and other credible sources relevant to the topic. The findings indicate that slang is used as a form of self-expression, group identity, and a more casual and creative means of communication. The use of slang provides several positive impacts, including enriching language variation, enhancing linguistic creativity, and strengthening social interactions in digital spaces. However, excessive use of slang may reduce the use of standard Indonesian, increase instances of code-mixing, and affect formal language proficiency among younger generations. Therefore, collaboration among the government, educational institutions, families, and society is essential to foster awareness of proper language use without hindering creativity in communication. In this way, the Indonesian language can continue to develop, remain relevant, and maintain its position as a symbol of national identity amid the currents of digital globalization.